PENGARUH PENERAPAN MODEL SSCS (SEARCH, SOLVE, CREATE, AND SHARE) BERBASIS GAMIFIKASI TERHADAP PEMAHAMAN KONSEP FISIKA SISWA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the implementation of the gamification-based Search, Solve, Create, and Share (SSCS) learning model on students' understanding of physics concepts at MAN 4 Pidie. The main problem behind this study is the low level of student engagement and procedural understanding of concepts in physics subjects. The research method used is a quasi-experimental with a Non-equivalent Control Group Design. The research sample consisted of 60 students divided into an experimental class (n = 30) and a control class (n = 30). The research instrument used a concept understanding test in the form of validated reasoned multiple-choice questions. The results of data analysis showed that the average post-test score of the experimental class reached 86.4, significantly higher than the control class of 70.2. Hypothesis testing using the Independent Sample T-Test produced a significance value of 0.000 (<0.05), which means there was a real effect of the treatment given. The improvement in student abilities in the experimental class was in the High category with an N-Gain value of 0.76, while the control class was in the medium category (0.48). The integration of gamification elements such as a point system and leaderboard was proven to be effective in increasing intrinsic motivation and retention of students' conceptual understanding. The conclusion of this study is that the gamification-based SSCS model is very effective in improving the quality of physics learning at the Madrasah Aliyah level.